2007
DOI: 10.1001/jama.297.4.367
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Citalopram and Interpersonal Psychotherapy on Depression in Patients With Coronary Artery Disease

Abstract: INCE THE EARLY 1990S, STUDIES have reported prevalences of major depression between 17% and 27% in hospitalized patients with coronary artery disease (CAD). 1 Most have also demonstrated that depression has a negative cardiac prognostic impact. 2,3 Only 1 large randomized trial, the Enhancing Recovery in Coronary Heart Disease (ENRICHD) study, 4 has tried to determine whether treating depression could improve cardiac prognosis in CAD patients. Although ENRICHD demonstrated that a combination of short-term indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 582 publications
(154 citation statements)
references
References 57 publications
3
145
1
5
Order By: Relevance
“…The SADHART and CREATE trials of antidepressants in depressed cardiac patients both showed the response rates for drug versus placebo were greater in patients who had a prior history of MDD, whereas patients experiencing their first major depressive episode showed no difference between drug and placebo (Lesperance, 2007;Glassman, 2002). It remains unclear whether this lack of greater drug response compared to placebo in the incident depressed group represents a different etiology of that depression (such as depression reactive to coronary disease severity, or vascular depression), thus explaining resistance to traditional depression treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The SADHART and CREATE trials of antidepressants in depressed cardiac patients both showed the response rates for drug versus placebo were greater in patients who had a prior history of MDD, whereas patients experiencing their first major depressive episode showed no difference between drug and placebo (Lesperance, 2007;Glassman, 2002). It remains unclear whether this lack of greater drug response compared to placebo in the incident depressed group represents a different etiology of that depression (such as depression reactive to coronary disease severity, or vascular depression), thus explaining resistance to traditional depression treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, CBT, in contrast to antidepressants, did not improve the cardiac outcomes (71). Also, the CREATE trial, in addition to studying citalopram, found that interpersonal psychotherapy did not improve depressive symptoms, compared to active controls (63).…”
Section: Psychotherapymentioning
confidence: 99%
“…Similarly, the Cardiac Randomized Evaluation of Antidepressant and Psychotherapy Efficacy (CREATE) trial introduced citalopram as a safe and efficacious agent for patients with depression (63). It has been also shown that escitalopram can reduce the risk of post-ACS depression and improve quality of life among patients with ACS and depression (64,65).…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Dans cette étude « randomisée » contrôlée, effectuée auprès de 2 481 patients dans plusieurs centres hospitaliers et universitaires des États-Unis, les bénéfices du traitement psycho logique semblent disparaître après 30 mois. De plus, il n'y a pas de différence entre le groupe de traitement et le groupe témoin sur les taux de réhospitalisation ou de décès causés par des complications cardiaques subséquentes (Carney et al, 2004 ;ENRICHD, 2003 Lespérance et al, 2007). Comme leurs collègues américains, ils ont conclu que leur traitement psychologique n'a pas d'effet significatif sur la dépression des patients et que l'antidépresseur citralopam s'avère supérieur au traitement psychologique dans la gestion des symptômes de dépression.…”
Section: Traitement De La Dépressionunclassified